2010
DOI: 10.1002/app.32238
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and conductivity performance of hyperbranched polymer electrolytes with terminal ionic groups

Abstract: Hyperbranched polymer was synthesized from pentaerythritol (as the central core), 1,2,4-trimellitic anhydride, and epichlorohydrin, and then hyperbranched polymer electrolytes with terminal ionic groups were prepared by the reaction of hyperbranched polymer with Nmethyl imidazole. The chemical structure, thermal behavior, and ionic conductive property of the hyperbranched polymer electrolytes were investigated by 1 H-NMR, FTIR, differential scanning calorimetry, thermogravimetric analyzer, and complex impedanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…By using a series of sequential reactions of pentaerythriol with trimellitic anhydride and epichlorhydrin, three generations of hyperbranched polyesters with terminal chloride groups were synthesized. Subsequent quaternization of chloride groups with N -methyl imidazole resulted in three different generations of poly­(ionic liquid)­s with 24, 32, and 56 terminal imidazolium groups with chloride or hexafluorophosphate as counteranions (Figure a) . The ionic conductivity of compounds with terminal imidazolium hexafluorophosphate ions increases with an increasing number of ionic groups to reach 4.9 × 10 –3 S cm –1 at 80 °C due to the higher free volume of randomized structures.…”
Section: Structure and Assembly Of Poly- And Oligo(ionic Liquid)smentioning
confidence: 99%
See 1 more Smart Citation
“…By using a series of sequential reactions of pentaerythriol with trimellitic anhydride and epichlorhydrin, three generations of hyperbranched polyesters with terminal chloride groups were synthesized. Subsequent quaternization of chloride groups with N -methyl imidazole resulted in three different generations of poly­(ionic liquid)­s with 24, 32, and 56 terminal imidazolium groups with chloride or hexafluorophosphate as counteranions (Figure a) . The ionic conductivity of compounds with terminal imidazolium hexafluorophosphate ions increases with an increasing number of ionic groups to reach 4.9 × 10 –3 S cm –1 at 80 °C due to the higher free volume of randomized structures.…”
Section: Structure and Assembly Of Poly- And Oligo(ionic Liquid)smentioning
confidence: 99%
“…Examples of hyperbranched polymer-based poly­(ionic liquid)­s with cationic and anionic end groups. (a) Pentaerythritol-based HBP PIL . (b) Polyglycerol-based HBPIL .…”
Section: Structure and Assembly Of Poly- And Oligo(ionic Liquid)smentioning
confidence: 99%
“…Hyperbranched polymers are also interesting materials as a polymer electrolyte because they possess lower T g , are highly soluble and processible, and have many branch ends, which could greatly enhance the ionic transport [17]. Itoh and coworkers [18,19] have reported that the polymer electrolytes based on hyperbranched polymer poly[bis(triethylene glycol)benzoate] with lithium salts (LiN(CF 3 SO 2 ) 2 and LiN(CF 3 CF 2 SO 2 ) 2 ) exhibit high ionic conductivity coupled with good electrochemical and thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…The collapse of PNIPAM chains above LCST causes increase in adhesion and elastic modulus as a result of the combination of dehydration and chain entanglement. Moreover, the incorporation of asymmetric composition of functional terminal groups can produce interesting morphologies by shifting the phase boundaries. For example, hyperbranched polyethers possessing homogenous peripheral chemical composition did not self-organize into ordered structures, while hyperbranched polyethers partially terminated with benzoyl groups formed macroscopic aggregates . However, to date, the majority of HBPIL studies focused on the synthesis and morphologies of HBPILs composed of symmetric chemical composition ,, with less attention paid to the assembly of HBPILs at interfaces. , It has been shown that amphiphilic branched polymers at the air–water interface exhibit interesting morphological transition upon lateral compression. , For example, poly­(styrene)- block -poly­(acrylic acid) dendrimer-like copolymers underwent “pancake-to-brush” transition under compression . Peculiar rod-to-globule and pancake-to-island transitions were also observed from brush block copolymers. , …”
Section: Introductionmentioning
confidence: 99%